Advances in Natural-Product-Based Fluorescent Agents and Synthetic Analogues for Analytical and Biomedical Applications - Soniya Joshi; Alexis Moody; Padamlal Budthapa; Anita Gurung; Rachana Gautam; Prabha Sanjel; Aakash Gupta; Surya P. Aryal; Niranjan Parajuli; Narayan Bhattarai (Bioengineering)
Fluorescence is a remarkable property exhibited by many chemical compounds and biomolecules. Fluorescence has revolutionized analytical and biomedical sciences due to its wide-ranging applications in analytical and diagnostic tools of biological and environmental importance. Fluorescent molecules are frequently employed in drug delivery, optical sensing, cellular imaging, and biomarker discovery. Cancer is a global challenge and fluorescence agents can function as diagnostic as well as monitoring tools, both during early tumor progression and treatment monitoring. Many fluorescent compounds can be found in their natural form, but recent developments in synthetic chemistry and molecular biology have allowed us to synthesize and tune fluorescent molecules that would not otherwise exist in nature. Naturally derived fluorescent compounds are generally more biocompatible and environmentally friendly. They can also be modified in cost-effective and target-specific ways with the help of synthetic tools. Understanding their unique chemical structures and photophysical properties is key to harnessing their full potential in biomedical and analytical research. As drug discovery efforts require the rigorous characterization of pharmacokinetics and pharmacodynamics, fluorescence-based detection accelerates the understanding of drug interactions via in vitro and in vivo assays. Herein, we provide a review of natural products and synthetic analogs that exhibit fluorescence properties and can be used as probes, detailing their photophysical properties. We have also provided some insights into the relationships between chemical structures and fluorescent properties. Finally, we have discussed the applications of fluorescent compounds in biomedical science, mainly in the study of tumor and cancer cells and analytical research, highlighting their pivotal role in advancing drug delivery, biomarkers, cell imaging, biosensing technologies, and as targeting ligands in the diagnosis of tumors.